2021
DOI: 10.3390/ijms22063095
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor Antagonist Mifepristone Does Not Alter Innate Anxiety-Like Behavior in Genetically-Selected Marchigian Sardinian (msP) Rats

Abstract: Marchigian Sardinian alcohol-preferring (msP) rats serve as a unique model of heightened alcohol preference and anxiety disorders. Their innate enhanced stress and poor stress-coping strategies are driven by a genetic polymorphism of the corticotropin-releasing factor receptor 1 (CRF1) in brain areas involved in glucocorticoid signaling. The activation of glucocorticoid receptors (GRs) regulates the stress response, making GRs a candidate target to treat stress and anxiety. Here, we examined whether mifepristo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…Case in point, Marchigian Sardinian alcohol preferring (msP) rats (a genetically selected rat model of AUD with phenotypic trait resembling anxiety and stress-related disorders such as PTSD) were less responsive to mifepristone's ability to reduce alcohol self-administration 78 or anxiety-like behaviour and startle responses. 79 Our results are also consistent with the previous baboon study where mifepristone did not reduce alcohol consumption, 18 supporting the hypothesis that in an individual with severe AUD who consumes large amounts of alcohol, mifepristone pharmacokinetics may be non-linear. In summary, given (1) the floor effect during the alcohol self-administration in the bar laboratory; (2) the unlikely ability that naturalistic drinking may be changed in an AUD population of non-treatment seekers; (3) the known differences between treatment-seekers versus non-treatment seekers for AUD 80 ; (4) the fact that, unlike in our study, previous work 14 reported an effect of mifepristone in reducing alcohol drinking in people with AUD; and…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Case in point, Marchigian Sardinian alcohol preferring (msP) rats (a genetically selected rat model of AUD with phenotypic trait resembling anxiety and stress-related disorders such as PTSD) were less responsive to mifepristone's ability to reduce alcohol self-administration 78 or anxiety-like behaviour and startle responses. 79 Our results are also consistent with the previous baboon study where mifepristone did not reduce alcohol consumption, 18 supporting the hypothesis that in an individual with severe AUD who consumes large amounts of alcohol, mifepristone pharmacokinetics may be non-linear. In summary, given (1) the floor effect during the alcohol self-administration in the bar laboratory; (2) the unlikely ability that naturalistic drinking may be changed in an AUD population of non-treatment seekers; (3) the known differences between treatment-seekers versus non-treatment seekers for AUD 80 ; (4) the fact that, unlike in our study, previous work 14 reported an effect of mifepristone in reducing alcohol drinking in people with AUD; and…”
Section: Discussionsupporting
confidence: 91%
“…The lack of mifepristone effect during the naturalistic drinking (outpatient setting) could be due to our sample being individuals with high family history of AUD and history of early trauma. Case in point, Marchigian Sardinian alcohol preferring (msP) rats (a genetically selected rat model of AUD with phenotypic trait resembling anxiety and stress‐related disorders such as PTSD) were less responsive to mifepristone's ability to reduce alcohol self‐administration 78 or anxiety‐like behaviour and startle responses 79 . Our results are also consistent with the previous baboon study where mifepristone did not reduce alcohol consumption, 18 supporting the hypothesis that in an individual with severe AUD who consumes large amounts of alcohol, mifepristone pharmacokinetics may be non‐linear.…”
Section: Discussionmentioning
confidence: 99%
“…This greater efficacy of mifepristone in dependent rats is in line with previous studies likely reflecting increased CeA GR function in alcohol dependence and protracted withdrawal ( Vendruscolo et al, 2015 ). Indeed, mifepristone has been shown to be most efficacious in reducing excessive alcohol drinking in animal models of binge-like drinking, heavy drinking, and alcohol dependence all of which are strong stressors per se while mixed effects of mifepristone on alcohol consumption or anxiety-related behaviors in non-dependent animals as well as in strains genetically-selected for innate high anxiety levels such as the Marchigian Sardinian rats have been reported ( Benvenuti et al, 2021 ; Calvo and Volosin, 2001 ; Fahlke et al, 1995 ; Holtyn and Weerts, 2019 ; Jacquot et al, 2008 ; Koenig and Olive, 2004 ; Newman et al, 2018 ; O’Callaghan et al, 2005 ; Ostroumov et al, 2016 ; Repunte-Canonigo et al, 2015 ; Savarese et al, 2020 ; Simms et al, 2012 ; Vendruscolo et al, 2015 ; Vendruscolo et al, 2012 ; Vozella et al, 2021 ; Yang et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety-like behaviour was assessed using novelty-induced hypophagia (NIH) procedures as previously described (Vozella et al, 2021).…”
Section: Novelty-induced Hypophagiamentioning
confidence: 99%